LEGAL CONSEQUENCES FOR LICENSEES IN THE EVENT OF INTELLECTUAL PROPERTY RIGHT (IPR) OWNER BANKRUPTCY - Maharani, Dhea Yulia; Bakir, Herman (Ridwan Institute, 2024)
This research discusses the legal consequences that arise for licensees when the owner of Intellectual Property Rights (IPR) experiences bankruptcy. The background of this research is the legal uncertainty regarding the fate of licenses granted by an IPR owner declared bankrupt, considering that the assets of the owner, including IPR, become part of the bankruptcy estate. The research method used is normative legal research, with a legislative approach and analysis of relevant court decisions. This research also uses secondary data in the form of related legal literature. The findings indicate that the bankruptcy of the IPR owner can potentially affect the rights and obligations of the licensee, especially concerning the continuity of the granted license. In some cases, the curator handling the bankruptcy estate has the authority to decide to continue or terminate the license agreement. However, legal protection for the licensee depends on the content of the license agreement and applicable legal provisions. Thus, the licensee is at risk of losing their licensing rights if there is no clear provision in the agreement or adequate legal protection from the law. This research recommends clearer regulations to protect licensees in situations where the owner of IPR experiences bankruptcy.